HEAVY METAL TOXICITY IN FISHES OF POLLUTED LAKES OF DHAKA CITYAND ITS IMPACTS ON HUMAN HEALTH - Abedin, Md. Joynal; Arafin, Sk. Abdul Kader; Akter, Shirin; Rahman, M.A.; Rahman, M. Obaidur (European Scientific Journal, ESJ, 2015)
The City of Dhaka is not built up plan wise from the beginning yet till date. The land uses are not following the urbanization rules correctly. Due to the laggings of proper water and air flow and basic treatment of household and industrial utilizing water, some of the major health issues are concerned. This research works is on the focus of heavy metal contamination in fishes of two major lakes in Dhaka city called Dhanmondi Lake and Gulshan Lake. The research is focusing mainly the study on Cr, Cd and Pb concentration in fishes along with other elements. Concentration of Cr is found in ranges of 3.45 μg/gm – 10.25 μg/gm, Cd is 2.17 μg/gm – 9.78 μg/gm and Pb is 1.132 – 7.102 μg/gm. The major element K and Ca with other trace elements are also projected. The data acquisition setup is calibrated using 2.2 MeV proton beam in the current ranges of 5nA to 15nA. The Van-de Graff Accelerator of Atomic Energy Centre, Dhaka has been used for sample irradiation. The IBA technique Proton Induced X-ray Emission (PIXE) has been applied using Si(Li) detector (SL30165) and other ORTEC nuclear electronics. The calibration and standardization of PIXE setup has been done using X-ray source, and IAEA standard CuSx (thin), Soil-7 (thick).